2019
DOI: 10.1152/ajpgi.00262.2018
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of reserve intestinal epithelial stem cells following severe ischemic injury

Abstract: Intestinal ischemia is an abdominal emergency with a mortality rate >50%, leading to epithelial barrier loss and subsequent sepsis. Epithelial renewal and repair after injury depend on intestinal epithelial stem cells (ISC) that reside within the crypts of Lieberkühn. Two ISC populations critical to epithelial repair have been described: 1) active ISC (aISC; highly proliferative; leucine-rich-repeat-containing G protein-coupled receptor 5 positive, sex determining region Y-box 9 positive) and 2) reserve ISC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…towards the crypt base, with an architectural preservation of the crypts [7]. These findings stand in line with the theory that following tissue insult the potent regeneration area is preserved, as the crypts are assumed to inhabit the ISCs.…”
Section: Academic Journal Of Pediatrics and Neonatologysupporting
confidence: 88%
“…towards the crypt base, with an architectural preservation of the crypts [7]. These findings stand in line with the theory that following tissue insult the potent regeneration area is preserved, as the crypts are assumed to inhabit the ISCs.…”
Section: Academic Journal Of Pediatrics and Neonatologysupporting
confidence: 88%
“…It is also worth mentioning, that there are two distinct ISC populations: Crypt base columnar (CBC) cells, which are actively proliferating and reserve intestinal stem cells (rISC) that are quiescent stem cells until activated upon injury. In line with this, Gonzalez et al (37) showed that Hopx + cells (rISC) are resistant to injury and are the likely source of epithelial renewal following prolonged ischemic injury (37).…”
Section: Intestinal Epithelial Wound Healingmentioning
confidence: 94%
“…In addition, by modulating spheroid size, oxygen availability (and thus, normoxia/hypoxia) in the spheroid core can be modulated to a certain extent. Such platforms have been used to study the mechanism of IRI, the role of SCs in the regeneration process, and to produce biologics with potential therapies in renal (Xu et al, 2016;, hepatic (Sun et al, 2018;Olander et al, 2019), intestinal (Gonzalez et al, 2019), cardiovascular (Chen et al, 2007;Suzuki et al, 2019;Sfriso and Rieben, 2020), lung (Pagano et al, 2017), skin (Park et al, 2017), fat (Mineda et al, 2015), and neural (Davenport Jones et al, 1998;Serganova et al, 2004;Fu et al, 2015;Liu et al, 2015;…”
Section: Spheroids and Irimentioning
confidence: 99%
“…To study intestinal IRI, porcine intestinal epithelial stem cells (ISCs) were harvested after a prolonged duration of vascular occlusion to guarantee deep epithelial loss. Afterward, spheroid cultures were established to determine the impact of different durations IRI (1-4 h) on ISCs in vitro and in the ischemic crypt and the contribution of these cells to mucosal repair (Gonzalez et al, 2019). This study highlighted a closely related behavior of ISCs in both 3D in vitro and in vivo platforms based on the expression profile of the genes leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5), SOX9 Lrig HOPX.…”
Section: Reperfusion Damagementioning
confidence: 99%